1891 N.C. Sess. Laws 775 - (:unkn) unknown (My University, 1891)
Ch. 52, § 27.: That they may prohibit the firing of any gun, pistol, fire-cracker, gunpowder, other materials or other dangerous combustibles in the streets, public grounds or elsewhere in said town.
Keywords: DISCHARGE